Frami® Software Protocol for Taekwondo: Development, Reliability and Reproducibility [Protokół Oprogramowania Frami® Dla Taekwondo: Rozwój, Niezawodność I Odtwarzalność] - Aedo-Munoz, E (Idokan Poland Association, 2021)
Background. The free combat software, called Frami®, has had its panel customized and adapted for Taekwondo analysis. Thus, the software is able to produce essential information from sequential combat actions and the functional demands of the combat. However, its protocol has not been validated for the sport of Taekwondo. Aims. The present study aimed to verify the objectivity and reliability of a technical-tactical and motor actions analysis protocol for elite-level Taekwondo competition using the Frami® software by comparing results from experts and non-expert evaluators. Methods. To determine if the Frami® software is suitable for Taekwondo competition, three evaluators (two experts and one non-expert) created a protocol, using displacement, attack, counterattack, defense, clinch, and pause phases, and selected 10 men s matches from the 2019 Taekwondo World Championships. A test-retest reliability was used to indicate the repeatability of test scores with the passage of time (test vs. retest after 24 hours). Cohen s Kappa and intraclass correlation coefficient were used to estimate and reflect the stability of the protocol measured by the Frami® software, p<.05. Results. After conducting an intraclass correlation coefficient (ICC) analysis, this study indicated that for all combat phases, the evaluators showed “moderate” to “excellent” reliability (ICC=.64 to. 99), except the third evaluator (non-expert) that presented “poor” for the clinch counterattack actions (ICC=.33). For objectivity, the obtained ICCs varied from “moderate” to “excellent” (ICC=.5 to. 99). For penalties and scores, objectivity was rated “almost perfect” (ICC =. 89 to. 97). Conclusion. The protocol proved to be reproducible and objective for the analysis of elite-level Taekwondo competition. This protocol was advantageous, since more motor actions were added (clinch, combat base, penalties, and scores) compared to the previously validated protocol, and it was developed under the current competitive rules in which electronic devices (chest, foot, and helmet) are used. However, the evaluation performed by a non-expert may not represent accurately the technical-tactical actions of the combat. © 2021 Idōkan Poland Association. All Rights Reserved.